Relationship of core stability with bowling speed in male cricket medium and medium fast bowlers - Pooja Chugh Anand; Gulshan Lal Khanna; Varsha Chorsiya; Geomon T.P (Al Ameen Medical College, 2017)
Background: A strong core muscles are believed to enhance athletic performance, few scientific studies have been conducted to identify the effectiveness of core stability on athletic performance especially in bowling speed in Medium and medium fast bowlers. The study aimed to examine the relationship between core stability and bowling speed in cricket medium and medium fast bowlers. Methods: 82 asymptomatic Cricket medium and medium fast bowlers participated in the study. The core stability was measured using a plank test and bowling speed was measured with a Radar speed gun. Result: The subject mean age, height, weight and BMI are 19.9+ 1.86 years, 172.47+6.2cm, 65.83+8.75 Kgs and 22.16+2.44 kg/m2 respectively. The mean values of Plank time and Bowling speed are 256.27+82.00 seconds and 109.43+ 7.04 Km/h. The result revealed a significant strong positive correlation (r=0.736, p<0.0001) core stability and the bowling speed. Discussion & Conclusion: Core stability is the ability to control the position and motion of the trunk over the pelvis and legs to allow optimum production, transfer, control of force and motion to the terminal segment in integrated kinetic chain activities. The subjects with well-developed core stability bowled significantly faster than the subjects with poorly-developed core stability.